Study of Solute Solvent Interaction Through Dielectric Properties of Allyl Chloride with Dimethyl Formamide using Time Domain Reflectometry Technique - G.M. DHARNE; A.P.MAHAROLKAR; S. S. PATIL; P.W. KHIRADE; S. C. MEHROTRA (International Journal of Pharma and Bio Sciences, 2010)
Dielectric relaxation measurements of Allyl Chloride (AC) with Dimethyl Formamide (DMF) mixture for different concentrations over the frequency range10MHZ to 20GHZ at 288K, 298K, 308 k & 318K have been carried out using Picoseconds Time Domain Reflectometry (TDR). Static permittivity (ε0), dielectric constant at high frequency (ε∞) and relaxation time (τ) were found through dielectric measurements. The Bruggeman factor (fB), Kirkwood correlation factor (geff), excess static permittivity (ε0E), and excess Inverse relaxation time (1/τ) E were determined and discussed to yield information on the molecular interaction and the Dynamics of the mixture of the system.